Splenic rupture post colonoscopy requiring splenectomy - Nguyen, Phi; Pretorius, Frans (International Surgery Journal, 2024)
Colonoscopy is a safe procedure performed routinely worldwide. Splenic rupture is a rare complication of colonoscopy with less than 100 case reports since 1974. We report a case of splenic rupture post colonoscopy requiring splenectomy, with a focus on the analysis of risk, investigation and treatment. A 60-year-old patient underwent a colonoscopy with polypectomy after a positive faecal occult blood test. After 19 hours, the patient experienced abdominal pain and dizziness. A computed tomography showed a splenic rupture and abdominopelvic hemoperitoneum. An urgent splenectomy was successfully performed. Physicians should have greater awareness of the possibility of splenic rupture following coloscopy to avoid delay in diagnosis and treatment for this life-threatening complication.